Boosting Boiler Efficiency Through Strategic Interventions: Meningkatkan Efisiensi Boiler Melalui Intervensi Strategis - Maydana, Adinda; Akbar, Ali (Procedia of Engineering and Life Science, 2024)
This study investigates the decline in steam boiler performance, focusing on identifying causal factors and implementing corrective actions. Employing an observational approach, the research highlights insufficient water supply and suboptimal fuel quality as primary contributors to decreased efficiency. Strategic measures, including optimizing air supply in the combustion process and enhancing corrosion control within the boiler's fire tubes, were implemented to address these issues. The findings suggest that these interventions effectively restore boiler performance, offering significant implications for maintenance practices and operational efficiency in industrial settings. Highlights: Steam Boiler Functionality: A steam boiler produces steam through fuel combustion and water conversion. Identifying Performance Factors: Lack of water filling and fuel quality are identified as factors causing boiler performance decline. Action Plan: Optimization of air in combustion and corrosion control in boiler pipes are implemented to address the performance issue. Keywords: Boiler, Corrosion, Performance